Nicotinic modulation of cortical circuits - Arroyo, Sergio; Bennett, Corbett; Hestrin, Shaul (Frontiers in Neural Circuits, 2014)
The ascending cholinergic neuromodulatory system sends projections throughout cortex and has been shown to play an important role in a number of cognitive functions including arousal, working memory, and attention. However, despite a wealth of behavioral and anatomical data, understanding how cholinergic synapses modulate cortical function has been limited by the inability to selectively activate cholinergic axons. Now, with the development of optogenetic tools and cell-type specific Cre-driver mouse lines, it has become possible to stimulate cholinergic axons from the basal forebrain and probe cholinergic synapses in the cortex for the first time. Here we review recent work studying the cell-type specificity of nicotinic signaling in the cortex, synaptic mechanisms mediating cholinergic transmission, and the potential functional role of nicotinic modulation.